Study on the impact resistance of polyurea-steel composite plates to low velocity impact - Jiang, Yuexin; Zhang, Boyi; Wei, Jianshu; Wang, Wei (International journal of impact engineering, 2019)
•Impact resistance of polyurea-steel composite plates to low velocity impact is researched experimentally and numerically.•A numerical simulation method for the simulation of the impact processes is introduced.•The mechanisms of the polyurea layers on the improvements of impact resistance of the composite plates are investigated and presented.•The relationships of the thicknesses of polyurea layers and the impact resistances of the composite plates are presented and discussed.•A parameter was introduced to characterize the energy absorption efficiency of the composite plates. Experimental and numerical studies on the response of polyurea coated steel plates to low velocity impact of a cylindrical hammer are presented in this paper. Low carbon steel plates were made and coated with polyurea layers to enhance their impact resistances. The polyurea-steel composite plates were constrained by a test rig and impacted by a blunt cylinder hammer using a drop weight machine. Numerical simulations of the impact processes were performed using the finite element code LS-DYNA. The numerical simulation method was validated by comparing its results with the experiments’. The experimental results showed that the polyurea coatings can effectively improve the ultimate energy absorption capacity of the steel plates. The decreasing order of the ultimate energy absorption capacity of the composite plates when coated with same thickness of polyurea layers was: the upper-side-coated plates, the double-side coated plates and the lower-side-coated plates. In order to quantify the energy absorption efficiency of the composite plates, a parameter Ed was proposed, and it was found that the composite plate coated with 4 mm polyurea on its upper side had the greatest value of Ed among all the plates.